BJPsych Open fifth anniversary editorial: history, accomplishments, trajectory and passion. Issue 4 (July 2020) - Kaufman, Kenneth R.
Summary: BJPsych Open has come of age. This editorial celebrates the journal's fifth anniversary by reviewing the history of BJPsych Open, what we have accomplished, where we strive to go (our planned trajectory) and the passion of being an Editor-in-Chief.